2013
DOI: 10.1155/2013/248749
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of South Moravian Floodplain Forests (Czech Republic) in Forest Environment Subject to Natural and Anthropogenic Change

Abstract: South Moravian floodplain forests at the confluence of the Morava and Dyje Rivers, which are related to the floodplain forests of Austria and Slovakia to a considerable degree, have been strongly affected by changes in forest environment caused by natural and anthropogenic impacts. The dominant change factors encompassed changes in the 12–14th centuries resulting in the formation of a flooded alluvium and a significant transition of hardwood floodplain to softwood floodplain. Their further development was affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
3
1
Order By: Relevance
“…The dam-induced impacts on the riparian plant communities were most conspicuous in the canopy and understory layers indicating their vulnerability. In contrary to the present findings, Klimo et al (2013) observed that the herb layer has shown the most resgistered responses due to changes in the groundwater table following river regulation. The negative influence of river regulation on the riparian vegetation can attribute to subsidence of the water table as riparian species in particular are sensitive to changes in groundwater levels (Webb and Leake, 2006).…”
Section: Density and Richnesscontrasting
confidence: 99%
“…The dam-induced impacts on the riparian plant communities were most conspicuous in the canopy and understory layers indicating their vulnerability. In contrary to the present findings, Klimo et al (2013) observed that the herb layer has shown the most resgistered responses due to changes in the groundwater table following river regulation. The negative influence of river regulation on the riparian vegetation can attribute to subsidence of the water table as riparian species in particular are sensitive to changes in groundwater levels (Webb and Leake, 2006).…”
Section: Density and Richnesscontrasting
confidence: 99%
“…However, such studies are lacking in Europe since it is almost impossible to find a primeval lowland floodplain area with an exclusively natural composition and structure. Therefore, we carried out this study in an area with one of the best preserved floodplain forest complex of pedunculate oak and narrow-leaved ash in Europe – Lonjsko Polje Nature park (LPNP) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Climate variability and extreme weather events have major influence on forest ecosystems over time (Kostić et al 2019), especially in climax tree species of floodplain forests (Klimo et al 2013). Pedunculate oak (Quercus robur L.), a key tree species with a wide geographic distribution is predominantly influenced by water supply, which varies between different microsites (Netsvetov et al 2017).…”
Section: Introductionmentioning
confidence: 99%